2016
DOI: 10.1080/09168451.2015.1123611
|View full text |Cite
|
Sign up to set email alerts
|

Destabilization of mayonnaise induced by lipid crystallization upon freezing

Abstract: The thermal and rheological history of mayonnaise during freezing and its dispersion stability after the freeze-thaw process were investigated. Mayonnaise was cooled to freeze and stored at -20 to -40 °C while monitoring the temperature; penetration tests were conducted on the mayonnaise, which was sampled at selected times during isothermal storage at -20 °C. Significant increases in the temperature and stress values due to water-phase crystallization and subsequent oil-phase crystallization were observed. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…tions Crystallization behavior is usually ascertained from the exothermic process under temperature-programmed cooling conditions where the sample temperature is lineally decreased using a DSC. As reported previously 13 , different phenomena occur in the non-isothermal process and during isothermal storage, and the shape of the endothermic peak derived from the melting of the lipid crystal also varies greatly. The differences can be ascribed to large and small degrees of supercooling in the non-isothermal process and during isothermal storage, respectively.…”
Section: Dsc Measurement Of Oil Under Non-isothermal Condi-supporting
confidence: 58%
See 1 more Smart Citation
“…tions Crystallization behavior is usually ascertained from the exothermic process under temperature-programmed cooling conditions where the sample temperature is lineally decreased using a DSC. As reported previously 13 , different phenomena occur in the non-isothermal process and during isothermal storage, and the shape of the endothermic peak derived from the melting of the lipid crystal also varies greatly. The differences can be ascribed to large and small degrees of supercooling in the non-isothermal process and during isothermal storage, respectively.…”
Section: Dsc Measurement Of Oil Under Non-isothermal Condi-supporting
confidence: 58%
“…Crystallization behaviors under non-isothermal conditions have been commonly investigated using differential scanning calorimetry DSC 17 , although we mainly investigated the induction period during isothermal storage to understand the processes transpiring during chilled or frozen storage of lipid-containing food. A difference in the melting behavior of rapeseed oil has been recognized between isothermal and non-isothermal storages 13 . However, insufficient knowledge in this area exists to reasonably explain the difference.…”
mentioning
confidence: 99%
“…We previously studied the crystallization behavior of rapeseed oil, which is a vegetable oil with a low melting point, particularly the time required for crystallization during isothermal storage, or the induction period of crystallization. In that study, stress measurement, temperature measurement, and differential scanning calorimetry (DSC) analysis revealed that several hours to half a day were required for complete crystallization during the isothermal storage of rapeseed oil at low temperatures (Miyagawa et al, 2015;Miyagawa et al, 2016). X-ray structural analysis showed minute structural changes during the induction period for crystallization and the crystalline polymorphism after crystallization (Miyagawa et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…Instability of an O/W emulsion is usually evaluated by measuring the formation of free oil layer (Gu et al, ; Le Denmat et al, ), change in turbidity (Aoki et al, ), mean oil‐droplet size (Aoki et al, ; Le Denmat et al, ), oil‐droplet size distribution (Katsuki et al, ), and volume fraction of oil after separation (Magnusson et al, ; Miyagawa et al, ). Measurements of turbidity and oil‐droplet size distribution would be inapplicable to mayonnaise‐like semisolid dressing, which contains less amounts of oil and more kinds of ingredients such as thickener and additional emulsifier than mayonnaise, because of its low dispersibility in water.…”
Section: Introductionmentioning
confidence: 99%